1975
DOI: 10.1021/bi00679a025
|View full text |Cite
|
Sign up to set email alerts
|

Translocation. XV. Characteristics of and structural requirements for the interaction of 24,25-dihydrofusidic acid with ribosome.elongation factor G complexes

Abstract: Fusidic acid inhibits polypeptide chain elongation by binding to the ribosome - elongation factor-G - GDP complex and thereby preventing its dissociation. The experiments reported here quantitate the interaction of the antibiotic [3H]-24,25-dihydrofusidic acid, an active analog of fusidic acid, with the ribosome - elongation factor-G - GDP comples. All components of the complex are essential for [3H]-24,25-dihydrofusidic acid binding. The stoichiometry of the interaction is ca. 1:1, and the Ka apparent, as det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
52
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 19 publications
3
52
0
Order By: Relevance
“…Some translation-targeting drugs lock the ribosome in long lived states via binding to translation factors. Among these is the steroid-like antibiotic fusidic acid (FA), 3 which stalls the ribosome in complex with EF-G and GDP (3). FA has low affinity to EF-G off the ribosome but forms a strong complex with ribosome-bound EF-G (3,4).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some translation-targeting drugs lock the ribosome in long lived states via binding to translation factors. Among these is the steroid-like antibiotic fusidic acid (FA), 3 which stalls the ribosome in complex with EF-G and GDP (3). FA has low affinity to EF-G off the ribosome but forms a strong complex with ribosome-bound EF-G (3,4).…”
mentioning
confidence: 99%
“…Among these is the steroid-like antibiotic fusidic acid (FA), 3 which stalls the ribosome in complex with EF-G and GDP (3). FA has low affinity to EF-G off the ribosome but forms a strong complex with ribosome-bound EF-G (3,4). EF-G plays double roles in bacterial protein synthesis by both catalyzing mRNA translocation during the peptide elongation cycle and, aided by ribosome recycling factor, splitting the post-termination ribosome into subunits (5) for a new round of initiation of mRNA translation (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fusidic Acid Binding-The studies of the EF-G function in the presence of FA has resulted in the conclusion that EF-G interaction with the ribosomes and consequent GTP hydrolysis may generate or uncover the FA binding site (31). Moreover, the addition of the ribosomes to EF-G and a GTP analog decreases the dissociation constant of the analog from the complex, which was found to be 59 nM (32).…”
Section: Discussionmentioning
confidence: 99%
“…FA binds with EF-G and retains it on the ribosome after GTP hydrolysis (23,31,32). For this reason, it was suggested that FA binds to EF-G in its intermediate conformation just after GTP hydrolysis (11).…”
Section: Discussionmentioning
confidence: 99%